On the question of the role of project management in the digital transformation of small and medium-sized businesses: essence and innovative potential - Bannikov, Valentyn; Lobunets, Tetiana; Buriak, Ievgen; Maslyhan, Olena; Shevchuk, Larysa (EDITORIAL PRIMMATE SAS, 2022)
Digital transformation is penetrating all areas of activities. This process is irreversible and poses challenges to businesses. The leading role for the successful digital transformation of small and medium-sized businesses is played by effective project management. The purpose of the article is to study the role of project management in the digital transformation of small and medium- sized businesses, to identify the key issues and the scenario of transformation, to outline the portrait of a project manager. Methods used: analysisб synthesis, graphic methods, the method of establishing cause-and-effect relationships. As a research result, theoretical aspects of project management and trends in understanding its role in the digital transformation of businesses were determined. The key questions for project management are outlined and its scenario is defined. The key skills and qualities of an effective project manager are described. The innovative potential of project management is considered. The scientific novelty of the research consists in clarifying the aspects necessary for effective project management, taking into account the trends in economic and sustainable development. The practical significance of the research results lies in outlining the areas of activity and improving the professional and extra-professional skills of project managers in the process of digital transformation.
Keywords: management; organization; soft skills; hard skills; sustainable development